Efectos del fosforo y azufre sobre el rendimiento de mazorcas, en una plantación de cacao (Theobroma cacao L.) ccn-51, en la zona de Babahoyo - Montes Mosquera, Marcelo Antonio (2016)
SUMMARY The work was carried out in the lands of the country property "María Cristina" located in the Enclosure "The Admiration" of the parish Febres-lamb, canton Babahoyo. It is located to 65 Km of the city in the road Babahoyo-Mata de cacao-San José of the Tambo. Eight treatments and three repetitions were investigated. The objective of this investigation was to evaluate the effects of the match and the sulfur kneads the yield of ears, in a plantation of cocoa. With this he/she settled down the quantity of alone fertilizers and necessary cocktails to maximize the yield, the effect of the treatments was evaluated on the yield of the ear and realize the respective economic analysis. He/she was carried out utilize DAP and ammonium sulfate; alone and cocktails, in parcels of 225 m2. The treatments were distributed at random in a design of complete blocks and for the evaluation of stockings the test was used from Tukey to 5 significancia%. At the end of the cycle of the cultivation diameter of Ear, longitude of Ear, number of Ears was evaluated by Tree, Index of Ear, Weight of Seed Dries off for Ear, Index of Seed for Ear, Yield for Plant, Yield for Hectare and Economic Analysis. The results determined that the phosphorus applications and sulfur influence, a bigger grain yield in the cultivation with more yield using DAP+ Sulfate of ammonium 30+40 kg/ha (1539,0 kg/ha).